Serological purification of polysaccharide antigens from Streptococcus mutans serotypes a and d: characterization of multiple antigenic determinants. - Linzer, R (1975)
The polysaccharide antigen preparations from serotype a and serotype d strains of Streptococcus mutans contained both a serotype-specific antigenic determinant and a common a-d antigenic determinant, as demonstrated by agar gel diffusion studies and a quantitative cross-precipitin assay. The chromatographically purified antigens were isolated by a method which depended on their serological specificity to determine if these two antigenic determinants were located on the same molecule. The a and d polysaccharides were recovered from specific antigen-antibody complexes and characterized with respect to their immunological specificity and chemical composition. Agar gel diffusion tests demonstrated that, in both the a and d preparations, the serotype-specific antigenic determinant and the common a-d antigenic determinant were present in one molecule.